Rhinoceromics: a multi-amplicon study with clinical markers to transferrin saturation levels in ex-situ black rhinoceros (Diceros bicornis michaeli) - Bruins-van Sonsbeek, Linda G. R.; Verschuren, Martie C. M.; Kaal, Sonja; Lindenburg, Peter W.; Rodenburg, Kees (C.) W.; Clauss, Marcus; Speksnijder, Arjen G. C. L.; Rutten, Victor P.M.G.; Bonnet, Bas F. J.; Wittink, Floyd (Frontiers in Microbiology, 2025)
Iron overload disorder (IOD) is a common condition in ex-situ black rhinoceroses (Diceros bicornis), although it has not been reported in the wild. This study aimed to gain a deeper understanding of the relationship between 25-hydroxy vitamin D [25(OH)D], inflammatory markers, insulin levels, the gut microbiome, dietary components, and transferrin saturation (TS) in ex-situ black rhinoceroses. Blood and fecal samples from 11 black rhinoceroses at five different European zoological institutions were monitored over a 1-year period. Inflammatory markers such as interleukin 6 (IL-6), serum amyloid A (SAA), interferon γ (IFN-γ), and tumor necrosis factor α (TNF-α) were analyzed. Our study corroborates the findings of previous research, which demonstrated that insulin, inflammatory markers, and TS% are higher in ex-situ black rhinoceroses compared to published wild ranges. Our data show no correlations between insulin, 25(OH)D, TS%, inflammatory markers, or short-chain fatty acids (SFCAs). Serum 25(OH)D exhibited significantly higher levels in summer than in winter. Transferrin saturation was influenced by age, which is consistent with previous studies. The microbiome did not differ significantly among individuals, institutions, sex, or season, unlike the mycobiome, which exhibited significant differences across institutions. The impact of the mycobiome differences on the physiology of the animals could not be determined from this study.